Progesterone Receptor Membrane Component-1 (PGRMC1) nucleolar localization in bovine granulosa cells and its putative interaction with nucleolin. (International Journal of Health, Animal Science and Food Safety, 2016)
PGRMC1 is a multifunctional protein that is found in multiple subcellular compartments, suggesting aspecific function at each site. Among the several subcellular sites of expression, PGRMC1 was found inthe nucleolus of human cells (Ahmad et al. 2009) and bovine zygotes (Luciano et al. 2010). However, therole at this site is not clear. Therefore, the aim of this study is to assess whether PGRMC1 modulatesnucleolar function. Immunofluorescence experiments confirmed nucleolar localization in ratspontaneously immortalized granulosa cells, bovine granulosa cells (bGC) and bovine oocytes.Moreover, in bGC PGRMC1 co-localizes with nucleolin, a well-known nucleolar marker exertingimportant functions within the nucleolus. Additionally, siRNA mediated gene knockdown experimentsshowed that when PGRMC1 expression is silenced, nucleolin localization shifts from the nucleolus to thenucleoplasm, suggesting a PGRMC1/nucleolin functional association. However, in situ proximity ligationassay did not detect a direct interaction between these two proteins, suggesting the involvement ofadditional molecules that could mediate PGRMC1/nucleolin interaction.In conclusion, these studies suggest a function for PGRMC1 in nucleolar activity and set the stage forfurther investigations aimed at dissecting PGRMC1’s molecular mechanisms of action in the nuclearcompartment.
Keywords: PGRMC1; nucleolus; nucleolin; bovine granulosa cells; ovarian follicle